Angiography and Cerebral Perfusion Scintigraphy in Balloon Test Occlusion of Carotid Artery in Head and Neck Tumors - Hertel, A.; Görling, S.; Schwager, K.; Hofmann, E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Surgery of head and neck tumors and other tumors involving the carotid artery may demand complete sacrifice of the carotid as part of the necessary tumor therapy. Sacrifice of the carotid may result in permanent brain perfusion damage. This uncorrectable procedure has to be tested beforehand in order to exclude this possibility.Materials and Methods: In order to predict this possible unstable hemodynamic brain perfusion damage, we evaluated 12 patients with head neck tumors prior to possible sacrifice of the carotid. The following tests were applied: angiography of the neck vessels, balloon test occlusion (BTO) of the carotid lasting 10 minutes combined with perfusion reserve testing using 1000 mg acetazolamide i. v. All patients received brain perfusion scintigraphy SPECT with Tc-99 m HMPAO injected during BTO. Results: All patient data were evaluated for clinical neurological defects under BTO. Perfusion of the great vessels was evaluated semiquantitatively for angiography (filling delay of the ophthalmic artery) and perfusion SPECT. None of the patients suffered from neurological defects. 9 /12 patients showed mild to severe perfusion defects. 9 /12 patients showed filling delays of more than1 second. Both tests showed a very good correlation (p = 0.005). Only 2 /12 cases were discrepant in one degree. All severe defects were congruent in both tests. Conclusion: None of the patients with severe defects underwent sacrifice of the carotid. Both tests resulted in increased security regarding the prediction of possible brain perfusion damage. The combination of angiography and brain scintigraphy is logistically easy and has a high value of prediction.
Keywords: angiography; SPECT; balloon insertions